Schistosoma mansoni and soil-transmitted helminths among schoolchildren in An-Nadirah District, Ibb Governorate, Yemen after a decade of preventive chemotherapy - Walid M. S. Al-Murisi; Abdulsalam M. Al-Mekhlafi; Mohammed A. K. Mahdy; Sami Ahmed Al-Haidari; Dhekra A. Annuzaili; Ahmed Ali Qaid Thabit (Public Library of Science (PLOS), 2022)
The Ministry of Public Health in Yemen continues the implementation of school and communitybased preventive chemotherapy with praziquantel and albendazole for the control and elimination of schistosomiasis and soil-transmitted helminths (STH). The latest remapping to update the distribution of schistosomiasis and STH was conducted seven years ago. This study aimed to estimate the prevalence, intensity and associated risk factors of Schistosoma mansoni and STH among schoolchildren in An-Nadirah District, Ibb Governorate, Yemen. A cross-sectional study was carried out among schoolchildren aged 615 years in four selected schools. Biological, demographic, socioeconomic and environmental data were collected using a pre-tested questionnaire. S. mansoni and STH eggs were detected and counted by the microscopic examination of Kato-Katz fecal smears. Out of 417 schoolchildren, 17.0% were infected with at least one intestinal helminth. Prevalence of S. mansoni and STH were 6.5% and 9.1%, respectively. The most prevalent parasite among STH was Ascaris lumbricoides (8.4%). Unemployed fathers (Adjusted Odds Ratio (AOR) = 3.2; 95% Confidence interval (CI): 1.23, 8.52; P = 0.018), eating exposed food (AOR: 2.9; 95%CI = 1.24, 6.89; P = 0.014), not washing hands before eating and after defecation (AOR: 4.8; 95%CI = 1.77, 12.81; P = 0.002), and schools located close to water stream (AOR: 22.1; 95%CI = 5.12, 95.46; P <0.001) were independent risk factors of ascariasis. Swimming in ponds/stream (AOR: 3.9; 95%CI = 1.63, 9.55; P = 0.002), and schools close to the stream (AOR: 24.7; 95%CI = 3.05, 200.07; P = 0.003) were independent risk factors of intestinal schistosomiasis. The present study does not indicate a reduction in the prevalence of intestinal schistosomiasis in this rural area since the latest remapping conducted in 2014, although ascariasis was reduced by half. The prevalence of the two parasites was highly focal in areas close to the valley, suggesting a significant role of the stream in sustaining and accelerating the parasitic infection. Children practicing swimming and having poor hygienic practices were at high exposure to S. mansoni and A. lumbricoides, respectively. Water, Sanitation and Hygiene intervention, schoolbased health education, and snail control, in addition to mass drug administration, will help in the interruption of transmission of schistosomiasis and STH.